Gender-based analysis of factors affecting junior medical students' career selection: addressing the shortage of surgical workforce in Rwanda - Grace Kansayisa; Sojung Yi; Yihan Lin; Ainhoa Costas-Chavarri (BMC, 2018)
Abstract Background There is a strong need for expanding surgical workforce in low- and middle-income countries. However, the number of medical students selecting surgical careers is not sufficient to meet this need. In Rwanda, there is an additional gender gap in speciality selection. Our study aims to understand the early variables involved in junior medical students' preference of specialisation with a focus on gender disparities. Methods We performed a cross-sectional survey of medical students during their clinical rotation years at the University of Rwanda. Demographics, specialisation preference, and factors involved in that preference were obtained using questionnaires and analysed using descriptive statistics and odds ratios. Results One hundred eighty-one respondents participated in the study (49.2% response rate) with a female-to-male ratio of 1 to 2.5. Surgery was the preferred speciality for 46.9% of male participants, and obstetrics/gynaecology for 29.4% of females. The main selection criteria for those who had already decided on surgery as a career included intellectual challenge (60.0%), interaction with residents (52.7%), and core clerkship experience (41.8%) for male participants and interaction with residents (57.1%), intellectual challenge (52.4%), and core clerkship experience (52.4%) for female participants. Females were more likely than males to join surgery based on perceived research opportunities (OR 2.7, p = 0.04). Male participants were more likely than their female participants to drop selection of surgery as a speciality when an adverse interaction with a resident was encountered (OR 0.26, p = 0.03). Conclusion This study provides insight into factors that guide Rwandan junior medical students' speciality preference. Medical students are more likely to consider surgical careers when exposed to positive clerkship experiences that provide intellectual challenges, as well as focused mentorship that facilitates effective research opportunities. Ultimately, creating a comprehensive curriculum that supports students' preferences may help encourage their selection of surgical careers.